Fitness participants perceived quality by age and practiced activity - Campos, Francisco (2017)
The fitness participants could have a specific and critical role in the service provision and, with that, contribute to the service quality improvement. The aim of this research is characterize and compare the quality indicators of the group exercise fitness instructor - through the participant’s perception, evaluated by QIF-AG questionnaire - considering their age and practiced activity. The data were collected from 622 group exercise participants (all from female gender, participants in fitness centers of Coimbra - Portugal, with 18 years old or more). After the application of the ANOVA one-way test is possible to conclude that, considering their age, there are statistical significant differences in 9 of the 11 items of the relational quality dimension and 9 of the 14 categories of the technical-pedagogical quality dimension. In accordance to the different dimensions [relational (F=11,820; p=0,001; ƞ2=0,037, small effect size); technical-pedagogical (F=8,029; p=0,001; ƞ2=0,025, small effect size)] and general construct (F=10,211; p=0,001; ƞ2=0,032, small effect size) is possible to conclude that are statistical significant differences considering the age of the fitness participants. In accordance to the activity, there are statistical significant differences in 8 of the 11 categories of the relational quality dimension and in 9 of the 14 categories of the technical-pedagogical quality dimension. Considering different dimensions [relational (F=6,106; p=0,001; ƞ2=0,038, small effect size); technical-pedagogical (F=4,207; p=0,006; ƞ2=0,027, small effect size)] and general construct (F=5,199; p=0,001; ƞ2=0,033, small effect size) also is possible to conclude that are statistical significant differences in the practiced activity.